The Correlation Between Students' Level of Anxiety and Their English-Speaking Skill - Prihandono (ASIAN PUBLISHER, 2023)
The purpose of this research is to find out empirical data about the correlation between students’ level of anxiety and their English speaking skill at the eight grade of MTs. Al-Kautsar Depok. This research used quantitative method through approach of correlation study. The research has taken empiric data especially the data of the students’ level of anxiety and their English speaking skill. The researcher had taken 190 students at the eight grade of MTs. Al-Kautsar Depok as the population. The sample of this research had taken from population consist of 24 students. The score of students’ level of anxiety was obtained from questionnaire that the researcher distributed, while the score of speaking skill was taken from the result of speaking test. The researcher used the Pearson Product Moment Test in hyphotesis testing and t-test to find out the correlations are significant or they only happen by chance. The result of this calculation found out that r=-0,656 while the t-test calculation found out tcount > ttable (-4,081>2,064). It means that Ho rejected. It shows that there is negative correlation between students’ level of anxiety and their English speaking skill. The determination coefficient is 43,1%. It means the students’ level of anxiety contributed 43,1% to the students’ speaking skill.Based on the statements above, it can be concluded that there is correlation between students’ level of anxiety and their English speaking skill at the eight grade of MTs. Al-Kautsar Depok.